Comparation of animal models of acute toxicity of doxorubicin - Bosanac, Milana; Andrejić Višnjić, Bojana; Samardžija, Golub; Amidžić, Jelena; Martić, Nemanja; Stefanović, Maja (Archive of Oncology, 2025)
Background: Animal models are essential for research in biomedicine. The cardiotoxicity of doxorubicin is the most common and severe side effect of this potent chemotherapeutic agent, and in order to investigate its prevention, a large number of studies have been performed on animal models. Unfortunately, the models are not uniform and the applied doses as well as the effectiveness vary significantly, often with great animal suffering.Methods: Male Wistar rats were divided into three groups of 10 animals each and treated with saline solution intraperitoneally (group C), or with doxorubicin intraperitoneally in a single dose of 15 mg/kg (group G15) or 20 mg/kg (group G20). Body weight, mortality, the condition of animals, intensity of lipid peroxidation, activity of antioxidant enzymes and myocardial tissue damage (using doxorubicin damage score, DDS) were analyzed.Results: Group 20, in comparison with groups G15 and C, exhibited the worse general condition, higher mortality and significantly higher intensity of lipid peroxidation. Both doses of doxorubicin induced a statistically significant decrease of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and glutathione-S-transferase (GST) activity compared to the control group. Among the doxorubicin-treated groups, GR is significantly more reduced in G15. GST is significantly more reduced in G20 while SOD and GSH-Px do not differ. The DDS score indicates myocardial tissue injury in both G15 and G20. Conclusions: Both applied doses induce animal models of acute doxorubicin induced oxidative stress and cardiotoxicity. A higher dose is more suitable for studies of oxidative stress, but should be applied with caution due to higher mortality. A lower dose is more suitable for studies focused on tissue morphology.
Keywords: Animal models, doxorubicin, cardiotoxicity, myocardium, oxidative stress